In search of the "Old Greek" in the Septuagint Psalter a case study of LXX Psalms 49 and 103 - Hong, Jonathan (2018)
Till today Rahlfs’s edition from 1931 is the standard text when it comes to the Greek Psalter. However, important discoveries were made after 1931, for example the Psalm scrolls from Qumran and early Greek manuscripts. This article includes the new material and argues that the original text of the Septuagint has been a freer translation than the text reconstructed by Rahlfs. It also shows that the new Greek manuscript findings of Papyrus Bodmer XXIV (Ra 2110) and Oxyrhynchus Papyrus 5101 (Ra 2227) attest to a particularly strongly Hebraized text-form.
Keywords: Bibel; Bibel; "Old Greek"